PENGARUH SUHU TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN LARVA IKAN MAS (Cyprinus carpio) - Dominggas M Kelabora (Berkala Perikanan Terubuk, 2010)
Cyprinus carpio has a particular optimum temperature for its appetite.Marine temperature increase and oxygen needs of organism is according to Van’tHoff law that every chemistry change, its reaction rapidity increase by twice tothird times every temperature increase of 10 °C.Treatment tested is in temperature of 26OC; 28OC; 30OC and 32OC.Parameter observed is fish relative weight growth, length increase and survivalrate.Research yield indicating that the relative weight growth (%) and larvaelength increase of highest gold fish (Cyprinus carpio) is that on temperature of28 OC) and according to equals Y = -56.597x2 + 3204x - 41537 it is known thatthe optimum temperature for larvae supervising of Cyprinus carpio is intemperature of 28.305OC.